POST-COVID-19 PANDEMIC RECOVERY OF HOUSEHOLD WELFARE - Marsus, Soffan; Ashari, Hasan; Nugrahanti, Trinandari Prasetya (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
This study aims to investigate the post-COVID-19 pandemic recovery on household welfare in the Greater Jakarta area a result of the government"™s policy of the enforcement of public activity restrictions (Pemberlakuan Pembatasan Kegiatan Masyarakat, PPKM). During the COVID-19 pandemic, there were numerous aspects of household affected, including household mobility, income, spending, and saving capability. There was a total of 400 respondents participated, who were the family breadwinners. The sampling methods employed were snowball and convenience sampling methods. The data was collected through a questionnaire distributed online using Google Forms. The results show that the PPKM implementation significantly affected the household welfare, and the recovery was proven in improved household mobility, income, spending, and saving capability following the COVID-19 pandemic. These findings suggest that the government must continue developing new and more effective policies while enhancing the anticipation and adoption of solution-oriented measures for the future.JEL: H31, I31, I38, H12.